Some Features of Youth Altruism Internalisation State - Lileikis, Saulius (Acta Paedagogica Vilnensia, 2007)
First of all spiritual and social man is necessary in the epoch of reappraisal virtues and new challenges of life. Contemporary society needs good teachers, doctors, businessmen and etc. But society consolidation, peaceful human coexistence, democratic communication and constructive cooperation development needs altruistic person, personality. Such personality expresses own spirituality and sociability. Initial spiritual human origin is expressed by altruism. Initial spiritual human origin is treated in contemporary society as an inborn one. The research aims to discover some features of youth altruism internalisation state by aspects of sex, class and living place. It was researched, did sex, class and living place have influence for altruism education of youth. It was discovered that just small part of youth understand the altruism as life not only for own sake, but for others’ sake, not adhere extreme, full categorical position of self-sacrifice. It must be admitted that not all respondents completely connected with altruism definition. Biggest part of them did not hear about altruism. Another part equate altruism with good even weak person. On the one hand youth did not learn definition of altruism in the school and family often, but on the other hand they have positive view at this value and it expression. At all it is dominate average and high levels of altruism experiences of both sexes. Girls’ emotional experiences of altruism are higher. Theirs positive feelings and experiences of altruism – little bit better. They feel pleasure connected with altruism expression often, it is important for girls to be necessary for another. Average level of youth altruistic behaviour is dominated by aspects of sex, class and living place. It is not natural regular taking part in public work and free aid for respondents. It was not fixed important distinctions of altruism features of youth by aspects of sex, class and living place. It is possible to help for youth to discover their spiritual dimension by cognitive level. It is necessary, that strategists of Lithuania education policy, scientists of educology and practicians should develop the technologies of altruism education.